English for Specific Purposes (ESP) e o ensino de termos no Curso Técnico em Informática Integrado ao Ensino Médio. - Heydt, Vanessa Spinelo (2019)
In recent years, there has been a national growth an increase in the demand for ELFE courses offer due to different factors. In this scenario, it has been noticed the need for teaching that prioritizes what the student must know in order to act properly in the use of the new language in a target situation. Specifically in the state of Paraná, one of the areas of English language teaching for specific purposes - English for Specific Purposes (ESP) - occurs in the technical courses offered by the State Secretariat for Education (SEED). In this specific context, there is some difficulty in the interrelation between the basic contents foreseen in the curriculum and the specific contents of the English language for the technical areas. Thus, the theme of this research is the teaching of terms in the Technician Course in Informatics Integrated to High School in a Paraná school from the ESP approach and its focus is the analysis of didactic materials for this purpose. To this end, the guiding questions were: i) The didactic materials of English for informatics selected to compose the analysis of this research contemplate the theoretical and methodological assumptions related to the ESP? ii) Do these works significantly contemplate the teaching of terminological units in the area? If so, in what way do they do it ?; iii) Among these books, which are characterized as appropriate pedagogical supports for the teaching of English for computer science taking into account contributions of teaching specific terms, associated to the approach of ESP in the Technical Course in Computer Science integrated to High School? In order to meet the purposes set out in this research, the theoretical reference is based on studies of Professional Education: Brazil (1996), Manfredi (2002), Paraná (2006), Ciavatta; Ramos (2011), Bezerra (2012); on the Teaching of Specialty Languages and ESP: Hutchinson; Waters (1987), Bloor (1997), Celani; Deyes; Holmes; Scott (2005), Ramos (2005, 2008), Celani; Freire; Ramos (2009), Enterría Sánchez (2009); and studies on terminology and terms: Cabré (1993, 1999, 2003, 2006), Barros (2004), Finatto; Krieger (2004), in addition to other researchers and documents. This research is inserted in the area of Applied Linguistics, and as regards its methodology, has a qualitative interpretative, documentary and exploratory character. The corpus of analysis consisted of a general English didactic material as well as informatics English textbooks and, from some established criteria, an analysis about the lexical exercises present in the works was performed. From this verification, it was concluded that the textbook Infotech – English for computer users by Cambridge publishing is appropriate to the needs of students learning of Technical Computer Science course integrated to High School. It can also be used by teachers as a complementary material as an integration possibility of basic contents in the curriculum and technical contents.